2010
DOI: 10.1002/cbf.1641
|View full text |Cite
|
Sign up to set email alerts
|

New volatile anesthetic, desflurane, reduces vitamin E level in blood of operative patients via oxidative stress

Abstract: It has been well known that some volatile anesthetic agents produce oxidative stress. Desflurane as a new volatile agent might have limited oxidative toxic effect because it is relatively a new short-acting anesthetic characterized by a short duration of action and a quick postanesthetic recovery. We investigated effect of desflurane on serum glutathione peroxidase (GSH-Px), lipid peroxidation (LP), vitamin E, and erythrocyte superoxide dismutase (SOD) values in patients. Fifteen adult patients are scheduled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Liver α-tocopherol levels decreased in enflurane exposed rats, although its levels were increased by vitamin E and selenium administration [14]. Eroglu et al [35] reported in a clinical study that serum α-tocopherol levels were decreased by desflurane. Plasma vitamin E results in the present study were confirmed by the previous experimental and clinical trials [13][14][15]35].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Liver α-tocopherol levels decreased in enflurane exposed rats, although its levels were increased by vitamin E and selenium administration [14]. Eroglu et al [35] reported in a clinical study that serum α-tocopherol levels were decreased by desflurane. Plasma vitamin E results in the present study were confirmed by the previous experimental and clinical trials [13][14][15]35].…”
Section: Discussionmentioning
confidence: 97%
“…Eroglu et al [35] reported in a clinical study that serum α-tocopherol levels were decreased by desflurane. Plasma vitamin E results in the present study were confirmed by the previous experimental and clinical trials [13][14][15]35]. The antioxidant enzyme system inherent in the cellular defense system is the most important defense mechanism against ROS.…”
Section: Discussionmentioning
confidence: 98%
“…It is preferred to cause minimal reactive oxygen species by using volatile anesthetic agents in low flow anesthesia (18). Especially in low flow anesthesia reactive oxygen species (ROS) are reduced due to the consumption of minimal sevoflurane and desflurane (19). Therefore, in low-flow anesthesia and lapa roscopic surgery morbidity and mortality are reduced (1,20).…”
Section: Discussionmentioning
confidence: 99%
“…Eroglu et al 19 reported that, desflurane causes oxidative stress by decreasing the value of vitamine-E in blood plasma. Erbas et al 20 stated that, total oxidant capacity is elevated in the patients who received desflurane.…”
mentioning
confidence: 99%
“…However, there are studies indicating that the agents which produce liver damage increases the activity of MPO 9,19,22 . Therefore we found that the desflurane increased the MPO activity in the liver tissue too.…”
mentioning
confidence: 99%